1975
DOI: 10.1002/j.1538-7305.1975.tb02879.x
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Glass-to-Metal Sealing on the Structure and Magnetic Properties of an Fe/Co/V Alloy

Abstract: Apparent changes in the coercivity and remanence of the magnetic reed material used in the remreed sealed contact were encountered during the glass‐to‐metal sealing operation. By using primarily metallographic observations correlated with magnetic data, it was determined that these changes were due to a modification of the 600°C‐aged microstructure caused by the time/temperature cycle experienced in sealing. The room‐temperature stable precipitates that are developed by the 600°C anneal to produce magnetic har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1976
1976
1976
1976

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…3 It was also found that the effects of this heating did not extend into the paddle section, and that there were no changes observed in this portion of the reed. Since the contact characteristics are much more sensitive to the paddle prop erties, the overall effect of the shank changes were relatively small and did not have a serious effect on switching performance of the sealed contact.…”
Section: Magnetic Materialsmentioning
confidence: 93%
“…3 It was also found that the effects of this heating did not extend into the paddle section, and that there were no changes observed in this portion of the reed. Since the contact characteristics are much more sensitive to the paddle prop erties, the overall effect of the shank changes were relatively small and did not have a serious effect on switching performance of the sealed contact.…”
Section: Magnetic Materialsmentioning
confidence: 93%